Improve body image and self-esteem of elementary school students by "Tiba-Tiba" gymnastics creation - Benedicta Setya Andriani; Akhmad Junaedi (Research and Development in Education (RaDEn), 2025)
This study aims to develop the creation of “Tiba-Tiba” gymnastics for elementary school students using popular children's songs to increase students' attention and engagement. The objectives of this study are: (1) Describe the development of gymnastics creation “Tiba-Tiba” that can improve the body image of elementary school students, (2) Describe the impact of gymnastics creation “Tiba-Tiba” on the feelings of self of elementary school students, (3) Identify the effectiveness of the ADDIE model in developing gymnastics creation “Tiba-Tiba” for extracurricular activities. The research method used is Research and Development (R&D) with the ADDIE model which includes analysis, design, development, implementation, and evaluation. The results showed that this exercise was able to improve students' body image and sense of self, which was seen from a straighter posture and a more cheerful facial expression after doing the exercise. This study provides important information regarding the successful application of the ADDIE model in the development of creative gymnastics to support the physical and psychological development of elementary school students.